Pengaruh Kreativitas dan Inovasi terhadap Keberhasilan Usaha Mikro di Kota Medan - Putri Nur Alfi Laili Fuad; Ahmad Rafiqi (Mahesa Research Center, 2026)
This study aims to analyze the influence of creativity and innovation on the success of micro businesses in Medan City. The problem raised in this study is that the success rate of micro businesses is still low even though the number of business actors continues to increase, so a deeper understanding of internal factors that affect business performance is needed. This study uses a quantitative approach with an associative method. Data was collected through the distribution of questionnaires to micro business actors and analyzed using multiple linear regression techniques. The results of the study show that creativity and innovation have a positive and significant effect on the success of micro businesses, both partially and simultaneously. In addition, innovation has a more dominant influence than creativity in increasing business success. These findings show that the success of a business is not only determined by the ability to generate ideas, but also by the ability of business actors to implement the idea effectively. Therefore, strengthening creativity and innovation needs to be the focus in efforts to empower micro businesses in a sustainable manner. words. Avoid referrals and unusual abbreviations. Cambria 10, with one line spacing (1) spacing. In Indonesian.